Karakteristik Fisik Ekstrudat dengan Perlakuan Penambahan Tepung Sagu pada Grits Jagung dan Suhu Barrel - Anggun Devi Yunistiana; Joko Nugroho Wahyu Karyadi; Devi Yuni Susanti; Iftinan Aribah Rati Inayah; Roihan Syafiq Mufadhol; Ailsa Saraswati Samodra; Dwi Ayuni (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2025)
The technology that is widely used in making snacks is extrusion. Most commercially available extruded products use corn grit as the main ingredient. Corn grits can be combined with high-starch ingredients such as sago. Sago has great potential to be developed considering that sago production in Indonesia is very high, but its use is still limited. Sago is usually only processed as traditional food, so further innovation is needed. Therefore, this research aims to examine the effect of sago composition (0%, 10%, 20%, 30%) and barrel temperature (120⁰C, 130⁰C, 140⁰C) on the characteristics of extrudates made from corn grit and sago starch. The extrusion process was carried out with a SYSLG-IV twin screw extruder. it was found that increasing the proportion of sago starch and barrel temperature causes an increase in the expansion ratio (3.21-3.81), WSI (2.78-11.49) and a decrease in water content (7.15-10.16), particle density (0.13-0.22), bulk density (0.07-0.11), WAI (5.94-6.6), and hardness (3.59-5.96). The best treatment based on TOPSIS analysis was the sample with a sago composition ratio of 30% and a temperature of 140⁰C